Aerosol optical depth observations by JARE-33 and JARE-34 in 1991 and 1992 - Kaneto,Susumu; Kishi,Takayuki; Meteorological Staff 33rd and 34th Japanese Antarctic Research Expedition (National Institute of Polar Research, 1994)
P(論文) To reveal the latitudinal distribution of atmospheric turbidity enhanced by the eruption of Mt. Pinatubo in June 1991 and Mt. Hudson in August 1991,aerosol optical depth at 5 wavelengths was observed with a portable sunphotometer (EKO MS-120) in November to December of 1991 and 1992. The observations were made from Tokyo to Syowa Station, east Antarctica on the icebreaker SHIRASE and on the route from Syowa Station to Dome-F, about 1000km inland. Another sunphotometer observation has been continued at Syowa Station since 1985. The main results of these observations are as follows. From onboard observations, aerosol optical depth at 500 nm in November and December of 1991 reached about 4 times the 1979 or 1987 level in the region of the equator. That of 1992 is still about 2 times the 1979 or 1987 level. The 1991 observations show two peaks corresponding to two volcanic eruptions. From Syowa Station observations, a remarkable increase of aerosol optical depth was seen in late 1991 and a gradual decrease followed it. The aerosol optical depth on the route from Syowa Station to Dome-F in October to December of 1992 is almost the same as that at Syowa although the largest distance was 1000 km. In early December of 1992,a temporary increase of aerosol optical depth was seen. departmental bulletin paper